1981
DOI: 10.1007/bf00235693
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacology of GABA-mediated inhibition of spinal cord neurons in vivo and in primary dissociated cell culture

Abstract: In this paper it is shown that the postsynaptic GABA-receptor chloride ion channel complex is composed of several functional subunits. There are probably at least two stereospecific locations on the receptor for GABA-binding and both must be occupied to obtain an increase in chloride conductance. The interaction between these sites is uncertain but there could be either positive cooperativity between the sites or only a requirement that both sites are occupied without occupation of either site affecting the af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1983
1983
2016
2016

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(1 citation statement)
references
References 168 publications
(181 reference statements)
0
1
0
Order By: Relevance
“…Efforts to interconvert the two populations of sites have been unsuccessful (Olsen et al,198 la). There appears to be no co-operativity between the two sites (Horng & Wong, 1979) although electrophysiological studies have suggested that at least two molecules of GABA may be required to bind and activate chloride transport (Macdonald & Young, 1981).…”
Section: Kinetics Ofreceptor Bindingmentioning
confidence: 99%
“…Efforts to interconvert the two populations of sites have been unsuccessful (Olsen et al,198 la). There appears to be no co-operativity between the two sites (Horng & Wong, 1979) although electrophysiological studies have suggested that at least two molecules of GABA may be required to bind and activate chloride transport (Macdonald & Young, 1981).…”
Section: Kinetics Ofreceptor Bindingmentioning
confidence: 99%